Convergence between the study of ecosystem services and nuclear technology – a necessary approach - Elaine Aparecida Rodrigues; Afonso Rodrigues Aquino; Amanda Rodrigues de Carvalho (Brazilian Journal of Radiation Sciences, 2021)
If in the 19th century scientific knowledge moved from a generalist perspective to a growing specialization, in recent decades, problems that transcend disciplinary and political boundaries have required solutions based on interdisciplinary research and global actions, which led to the establishment of the Sustainable Development Goals (SDGs). Viewing from the latter perspective, the study of ecosystem services has converged on a fast-growing, transdisciplinary area of knowledge, at the same time that the advances in the nuclear field have enabled applications in industry, health, agriculture and the environment. Considering the development of these two areas of knowledge, the objective of this study is to evaluate the correlation between Ecosystem Services (ES) and Nuclear Science and Technology (NST), by means of category building and content analysis applied to articles compiled from Web of Science. From 1980 to June 2020, 27,301 records (articles and reviews) were listed for the term “Ecosystem Service*”. When refining the result with the application of descriptors related to the nuclear field, correspondences were found for “Uranium”=14; “Nuclear Power”=6; “Nuclear Energy”=3; “Nuclear Technology*”=1; “Nuclear Fuel*”=1; “Nuclear Material*”=1; “Radiation”=7; “Isotope*”=188, totalizing 221 correspondences. On the other hand, 9,949 records were obtained for the same time interval, when using the descriptors for the nuclear field, plus the terms “Nature” or “Ecosystem*” or “Environment”. Despite attesting that NST truly converges on ES, this correlation needs to be made more explicit in ES studies, in order to expand the perspectives for the conservation, preservation and recovery of the ecosystem services and their contribution to human well-being.